Conflict-based speech error monitoring in bilinguals: Differences between first and second language monitoring. (August 2022) - Coulter, Kristina; Phillips, Natalie A.
Abstract: All speakers must monitor their speech for errors. However, few studies have investigated speech monitoring in bilinguals. We examined whether monolinguals and bilinguals differ in first (L1) and second (L2) language speech monitoring. Participants included 18 English monolinguals, 20 English-French and 21 French-English sequential bilinguals who learned their two languages one after the other, and 15 simultaneous bilinguals who learned their two languages from birth. All participants performed an English phoneme substitution task while an electroencephalogram (EEG) was recorded. Three event-related brain potential (ERP) components were analyzed: the stimulus-locked P200 and N200, and the response-locked error-related negativity. All groups performed the task equally well despite showing differences in ERP patterns on correct and incorrect trials. Only simultaneous bilinguals showed a larger P200 preceding incorrect compared to correct responses, suggesting a role for lexical activation processes in the production of speech errors. All language groups showed evidence of pre-articulatory, conflict-based error monitoring through the N200. Only French-English sequential bilinguals, in their L2, showed a reliable ERN effect following speech errors. Thus, speech error monitoring processes were found to be influenced by whether one is speaking in their L1 versus L2 depending on the stage of monitoring, with response conflict being more informative for post-articulatory error monitoring during L2 compared to L1 speech production. Highlights: Monolinguals and bilinguals show evidence of conflict-based speech error monitoring. Bilingualism itself does not influence speech monitoring processes (N200 and ERN). Post-articulation error monitoring (ERN) differs between first and second language. Response conflict is more informative for second vs first language error monitoring.